2013
DOI: 10.3352/jeehp.2013.10.5
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ perception of the educational environment in a medical college in India: a cross-sectional study using the Dundee Ready Education Environment questionnaire

Abstract: Purpose:The objective of this study was to assess student perceptions of the environment in this medical college using the Dundee Ready Educational Environment Measure (DREEM).Methods:Cross-sectional study; 348 medical student volunteers (68.1%) of all semesters participated (511 enrolled). DREEM has 50 items, each rated from 0–4 (Likert scale: 0, strongly disagree to 4, strongly agree), that measure five domains: students’ perceptions of learning; perceptions of teachers; academic self-perception; perceptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
97
2
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(120 citation statements)
references
References 19 publications
17
97
2
4
Order By: Relevance
“…These findings are different from the previous results of Kohli and Dhaliwal [35], which indicated that the DREEM score decreases as the school year increases. Our findings also differ from those of Demirören [36], who reported that the DREEM score is maximized in the third-year student group at the end of the preclinical stage and prior to entering practical sessions.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are different from the previous results of Kohli and Dhaliwal [35], which indicated that the DREEM score decreases as the school year increases. Our findings also differ from those of Demirören [36], who reported that the DREEM score is maximized in the third-year student group at the end of the preclinical stage and prior to entering practical sessions.…”
Section: Discussioncontrasting
confidence: 99%
“…Many institutions globally report similar concerns. Some researchers (Kohli & Dhaliwal, 2013;Hasan & Gupta, 2013;Khursheed & Baig, 2014) have reported not having a good support system for students who get stressed. [11][12][13] Al-Kabbaa et al (2012) has reported that students are too tired to enjoy the course.…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that such a change might provide students with stimulating opportunities for learning, thereby building confidence as well. 3,9,10 For the year 5 students, Bed-side teaching is an effective instrument to teach clinical skills, communication, ethics, empathy, and professionalism; however, in overburdened government hospitals such as ours, teachers are overwhelmed with patient care responsibilities. Added to that, overcrowded, noisy wards and outpatient departments also serve as obstructions to clinical teaching.…”
Section: Discussionmentioning
confidence: 99%
“…There are only limited studies undergone in medical colleges in Kerala and India. 3,9,12,13 in this regard. No studies regarding the medical students' perspective have been published from central Kerala so far.…”
mentioning
confidence: 90%
See 1 more Smart Citation